Shopee as a Marketing Media: User Generated Content, Brand Trust, and Perceived Usefulness on Azarine Skincare Purchasing Decision - Yulianto, Ramasandy Sundan; Makrus, Ahmad (International Journal of Business, Economics, and Social Development, 2025)
Considering the overclaim issue in the skincare sector, this study intends to assess, on the Shopee e-commerce platform, the influence of User Generated Content (UGC), Brand Trust, and Perceived Usefulness on purchasing decisions for Azaline skincare products. The context of this study is based on the fast expansion of e-commerce in Indonesia, the great popularity of skincare goods on Shopee, and the issue of overclaim that can influence consumer confidence. The literature study covers the ideas of UGC, Brand Trust, Perceived Usefulness, and Purchase Decisions together with their dimensions and signs. Data will be gathered in this quantitative study using a survey technique from customers who have bought Azarine goods on Shopee by means of questionnaires As well as to investigate the possible moderation or mediation effects of the overclaim phenomenon, multiple regression analysis will be used to evaluate the hypothesis about the influence of UGC, Brand Trust, and Perceived Usefulness on Purchase Decisions. By tackling the issue of overclaim, it is believed that the findings of this study would shed light on skincare companies in developing successful marketing plans and raising consumer confidence in the digital era.